2012
DOI: 10.22358/jafs/66140/2012
|View full text |Cite
|
Sign up to set email alerts
|

The nutritive value and phosphorus availability of yellow- and dark-seeded rapeseed cakes and the effects of phytase supplementation in broilers

Abstract: Three experiments on 242 Ross 308 broiler females were conducted to evaluate the nutritive value of expeller cakes cold-pressed from 3 yellow-seeded lines (YRC 041, 036, and 022) and black-seeded winter rape (BRC), and the effects of phytase supplementation. The total P content and phytase activity were similar in YRC and BRC and averaged 9.5 g/kg and 411 U/kg, respectively. Total glucosinolate contents in YRC were from 8.7 to 10.2 μmol/g dry matter (DM), in BRC, 12.6 μmol/g DM, in which progoitrin constituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The apparent discrepancy between different ATTDs (as the final effect of fibre digestion) and uniform colonic concentration of SCFAs (as its metabolites) may be explained by different rates of fibre fractions fermentation and absorption of fatty acids, which were not determined in our study. Our results in pigs are partly conform to the results of Czerwinski et al (2012), who evaluated the same rapeseed cakes in chickens and in one experiment found higher caecal propionate concentration in birds fed the BRC than the YRC diets. The effect of rapeseed on SCFA found in chickens in two different experiments were, however, inconsistent.…”
Section: R = Correlation Coefficientsupporting
confidence: 91%
See 4 more Smart Citations
“…The apparent discrepancy between different ATTDs (as the final effect of fibre digestion) and uniform colonic concentration of SCFAs (as its metabolites) may be explained by different rates of fibre fractions fermentation and absorption of fatty acids, which were not determined in our study. Our results in pigs are partly conform to the results of Czerwinski et al (2012), who evaluated the same rapeseed cakes in chickens and in one experiment found higher caecal propionate concentration in birds fed the BRC than the YRC diets. The effect of rapeseed on SCFA found in chickens in two different experiments were, however, inconsistent.…”
Section: R = Correlation Coefficientsupporting
confidence: 91%
“…Similar results were reported by Smulikowska et al (1998), who found that the total tract digestibility of protein in rapeseed cakes for rats was not affected by the type of rapeseed used, whereas in heat-treated meals it was higher in yellow than brown rapeseed meal. Moreover, in chicken, the protein digestibility of the same BRC and YRC as those used in our study did not differ (Czerwinski et al 2012).…”
Section: R = Correlation Coefficientmentioning
confidence: 48%
See 3 more Smart Citations